Towards a collaborative academic identity and culture: Teaching teams as innovation in university degree programs - Israel Alonso Sáez; Leire Darretxe; Nekane Beloki (Arizona State University, 2019)
This work delves into the value of teaching collaboration in higher education (HE). Based on a review of the international scientific literature, the a case study of a degree program in Social Education at the University of the Basque Country was carried out. For this case study, teaching teams were created and established each quarter for the duration of four years, revealing the potential for a more collaborative teacher identity and culture, as well as the difficulties and conditions necessary to advance forward. The results obtained are discussed in relation to other research studies and the value of working collaboratively within university education is affirmed.